Waldef a French romance from medieval England - Djordjević, Ivana ca. 20./21. Jh; Clifton, Nicole ca. 20./21. Jh (Arc Humanities Press, 2021)
This first English translation of Le Roman de Waldef makes a significant representative of the French literature of medieval England accessible for the first time. Its wide-ranging content provides an ideal introduction to a number of themes in medieval literature, making it suitable for a variety of undergraduate and graduate courses. The fast-moving romance plot of this early thirteenth-century tale recounts the ancestry and exploits of Waldef and his two sons, set against a history of pre-Conquest England. The narrative shares themes and incident types with other important insular romances, including the Lai of Haveloc, Boeve de Haumtone, and Gui de Warewic. Waldef's scope, interest in battle, and political stratagems bear reading alongside medieval chronicles, while secret love affairs connect it with other romance literature of the period, and adventures across a wide area of the known world provide affinities with medieval travel narrative
Keywords: LITERARY CRITICISM / Medieval; Romances -- Translations into English